A Simulation Approach to IoT Based Safety Keychain Device Using Proteus Software - Adan, Nor Faezah; Abdul Hakim, D. N. D.; Syed Jafri, S. S. E.; Sukelan, N. S.; Ahmad, M. S. (Multidisciplinary Applied Research and Innovation, 2020)
Nowadays there are many crimes like theft, robbery, rape cases, murder and others. These cases especially theft and rape are common among women. Hence, this project introduces a safety device for women which is easy to use and portable. This project aims at designing an IoT based safety device that relies on providing security to women. The applications used for this project consist of Proteus and Blynk app. The system is using Neo-6 GPS module with antenna as GPS tracker to track the location of the device. Arduino Uno replaces NodeMCU as the main controller that connects GPS tracker and push button to the Blynk app. The system works when an individual is in an emergency, they will press the switch on the device and automatically the light from the LED will turn on and the buzzer will make a sound and act as an alarm system. Blynk app is used to map location and send notification to immediate receivers in the form of blynk notification, email and twitter.